Psychological Social Capital in Balerante Community in Facing Merapi Eruption Disaster: Modal Sosial Psikologis pada Masyarakat Balerante dalam Menghadapi Bencana Erupsi Merapi - Ferdinanto, Ferdinanto; Triyono, Triyono (Psikologia : Jurnal Psikologi, 2025)
Balerante Village, located in Kemalang District, Klaten Regency, is included in the Disaster Prone Area (KRB) III of Mount Merapi, so it is at high risk of the impact of the eruption. On October 26, 2010, the eruption of Mount Merapi caused 347 deaths and 258 injuries, and economic losses amounted to Rp4.511 trillion. Social capital (psychological) is very important to increase community resilience in the face of disasters. This study aims to examine the social (psychological) capital of the people of Balerante Village, especially psychological attributes such as social support, social cohesion, and community involvement. The research method used was qualitative, with in-depth interviews with five informants and field observations. The results of the study show that the social (psychological) capital of the people of Balerante Village is built through social norms, networks between groups, and strong emotional attachments. The existence of Disaster Risk Reduction Organizations (OPRB) and Village-Owned Enterprises (BUMDes) is an important factor in risk mitigation and post-disaster economic recovery. In addition, the habit of mutual cooperation strengthens community solidarity and accelerates recovery. The shift from mystical beliefs to scientific approaches through the adoption of information technology is also improving disaster preparedness. The implications of this study confirm the importance of social (psychological) capital as a core element in community-based disaster mitigation strategies. These findings make a strategic contribution to the development of disaster mitigation policies based on strengthening social (psychological) capital. Highlights: Social Cohesion & Support – Strong emotional bonds and mutual cooperation enhance disaster resilience. Institutional Role – OPRB and BUMDes play a key role in mitigation and economic recovery. Shift to Science-Based Preparedness – Adoption of technology improves disaster response and reduces reliance on mystical beliefs. Keywords: Psychological Social Capital, Disaster Mitigation, Mutual Cooperation, Disaster Preparedness, Mount Merapi Eruption